Anesthetic Management of a Large Right Ventricular Mass due to Idiopathic Hypereosinophilic Syndrome in a Patient Undergoing Cardiac Surgery, a Case Report. (December 2022) - Scorsese, Giacomo; Hake, Austin; Christophides, Alexa; Poppers, Jeremy; Zabirowicz, Eric
Cardiovascular complications of hypereosinophilic syndrome (HES) constitute a significant source of morbidity and mortality, with heart involvement found in approximately 40%–80% of patients. In patients with right heart failure due to an intracardiac mass, induction of general anesthesia poses numerous challenges. The effects of positive pressure ventilation on right ventricular (RV) physiology can quickly lead to precipitous cardiovascular collapse, which increases the importance of maintaining adequate negative pressure ventilation strategies. Current strategies involve awake femoro-femoral cannulation with partial vs full flow femoro-femoral cardiopulmonary bypass (CPB), but both methods increase the risk of intraoperative blood loss due to systemic heparinization prior to sternotomy. In this case report, the authors describe an approach to anesthetizing a patient with severe right ventricular heart failure due to an intracardiac mass due to idiopathic HES. This approach involves femoral cannulation prior to induction of general anesthesia, airway topicalization, inhalational induction with fiberoptic intubation, and sternotomy with aortic/bicaval cannulation before paralysis.